Hereditary Undecidability of the Theory of Lattice-ordered Abelian Groups - Gurevich, Yuri (Algebra and Logic (Russian), 1967)
Delimiting the decidability result of [3] for linearly ordered abelian groups and answering Malcev's question, we prove the theorem in the title.